Propuesta de mejoramiento y optimización de los procesos de transporte y distribución de producto terminado de la fábrica de embutidos la Ibérica - Ramos Jara, Jorge Esteban (2020)
This work focused on designing a proposal for the improvement of the transport and distribution process of the finished product of the company La Ibérica, Cía. Ltda., which is a company dedicated to the manufacture of sausages that has satisfied part of the demand of the ecuatorian market for more than a century. In the theoretical development, the topic referring to the value chain and the supply chain of production processes and the tools used universally for the diagnosis of processes within organizations such as the VSM, the SIPOC and SCOR diagram. A diagnosis of the current situation of the transport and distribution process of the finished product of the company was made, it was evidenced that it incurs higher transport costs because despite having the necessary fleet of vehicles to reach the client In the end, their products do not cover all routes due to a lack of human resources, which has resulted in reports of dissatisfaction from customers. By proposing a simple transportation and distribution management model, it was determined that the company, using its transportation fleet and hiring personnel to carry out this activity, saves 3.187 USD per kilometer traveled it is currently USD 4.75 per kilometer and when implementing the proposal the cost per kilometer traveled would be USD 1.563, guaranteeing greater customer satisfaction since it has complete control of the process. In terms of cost per kilogram of transported product, you save 0.03 dollar /kilogram, equivalent to a reduction in your costs of 3.2percenaje per kilogram of transported product. In addition, the company will decrease its operating costs by 5.77 percentaje and increase its annual sales by 10.49percentaje . The company's VSM was prepared incorporating the proposed proposal, as well as a SIPCO diagram and SCOR diagram those reflects the improvement in the number of processes when incorporating the designed proposal.